Necessity Entrepreneurship - O’Donnell, Philip; Leger, Margot; O’Gorman, Colm; Clinton, Eric (Academy of Management Annals, 2024)
Over the past two decades, necessity entrepreneurs—those who engage in entrepreneurship because of a belief that decent or desirable livelihood alternatives do not exist for them—have become increasingly visible in the entrepreneurship literature. During this time, however, necessity entrepreneurship—both the phenomenon and the theoretical construct—has acquired something of a bad name. As a phenomenon, necessity entrepreneurship is widely associated with capital constraints, marginal profits, and limited economic impact. As a theoretical construct, it is often seen as a crude and pejorative classification device. In this article, we take stock of this emerging body of research, providing an integrative account of extant research and a focused analysis of the main areas of discord within this literature. We set out specific pathways aimed at remediating incongruity between, on the one hand, how necessity entrepreneurship is defined and conceptualized and, on the other, how it manifests across the diverse array of real-world contexts that feature in this literature. We use these reflections to foreground an agenda for future research which is sensitized to the main concerns and critiques that have surfaced in this literature in recent years and to key shifts in the conceptual approach to which they have given rise.